Digital discourse language in the new media - Thurlow, Crispin; Mroczek, Kristine R. (Oxford ; New York : Oxford University Press, 2011)
Chapters cover a range of communicative contexts (journalism, gaming, tourism, leisure, performance, public debate), communicators (professional and lay, young people and adults, intimates and groups), and languages (Irish, Hebrew, Chinese, Finnish, Japanese, German, Greek, Arabic, and French).
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sociolinguistics; Social media; Digital media; Technological innovations -- Social aspects; Discourse analysis -- Social aspects